2021
DOI: 10.1007/s12026-021-09192-6
|View full text |Cite
|
Sign up to set email alerts
|

Iodoprophylaxis and thyroid autoimmunity: an update

Abstract: Adequate iodine intake is necessary for normal thyroid function. Iodine deficiency is associated with serious complications, but also iodine excess can lead to thyroid dysfunction, and iodine supplementation aimed to prevent iodine deficiency disorders has been associated with development of thyroid autoimmunity. The epidemiology of thyroid diseases has undergone profound changes since the implementation of iodoprophylaxis, notably by means of iodine-enriched salt, specifically resulting in decreased prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 88 publications
1
24
0
2
Order By: Relevance
“…The incidence of postpartum thyroiditis has not directly been demonstrated to be associated with iodine status ( 61 ). However, some studies, but not all, observed an increased risk for TPO antibody positivity in iodine excess ( 60 , 62 , 63 ), which in turn is associated with postpartum thyroiditis. Three small randomized studies have examined the effects of prenatal iodine supplementation on postpartum thyroiditis, but none of the studies observed a difference in frequency or severity of the condition ( 61 , 64 , 65 ).…”
Section: Thyroid Function and Thyroid Disordersmentioning
confidence: 99%
“…The incidence of postpartum thyroiditis has not directly been demonstrated to be associated with iodine status ( 61 ). However, some studies, but not all, observed an increased risk for TPO antibody positivity in iodine excess ( 60 , 62 , 63 ), which in turn is associated with postpartum thyroiditis. Three small randomized studies have examined the effects of prenatal iodine supplementation on postpartum thyroiditis, but none of the studies observed a difference in frequency or severity of the condition ( 61 , 64 , 65 ).…”
Section: Thyroid Function and Thyroid Disordersmentioning
confidence: 99%
“…Due to the primary relevance of optimal sodium intake, as well as iodine supply, further updated prospective studies on the effects of salt restriction on iodine status are required. Anyhow, there is no doubt that a proper monitoring of iodoprophylaxis is mandatory, to ensure a sustained adequate iodine supply, and to avoid iodine excess, a possible risk of uncontrolled iodine prophylaxis, that may result in an increased incidence of thyroid autoimmunity [71][72][73].…”
Section: Discussionmentioning
confidence: 99%
“…An increased prevalence of antithyroid antibodies has been observed in residents in areas with iodine excess [38]. Salt iodination may induce the development of thyroid autoimmunity [39]. The presence of autoimmune thyroiditis has been associated with both iodine deficiency and iodine excess suggesting a U-shaped relationship between iodine status and thyroid autoimmunity risk in adults [40].…”
Section: Environmental Factorsmentioning
confidence: 99%